Pharmacoeconomic particulars of ovaries cancer's treatment - V N Zhurman; E V Eliseeva; L I Gurina; M V Volkov (IP Berlin A.V., 2015)
The appearance of cytostatics made a revolution in the treatment of malignant neoplasm's, allowing to make curable previously fatal diseases and prolong life for many patients with incurable tumors. Taking into account the steady growth of malignant neoplasms of the female reproductive system, including ovarian tumors, high rates of mortality in patients of reproductive age, and also the emergence of costly new anticancer drugs, allow to make a pharmacoeconomic analysis of ovaries cancer's treatment ways, to select the most effective and safe means in conditions limited health care resources.